PENGARUH KURS DOLLAR AMERIKA, KUNJUNGAN WISATAWAN, LAMA MENGINAP WISATAWAN, DAN RATA-RATA PENGELUARAN WISATAWAN TERHADAP EKSPOR KERAJINAN UKIRAN KAYU DI PROVINSI BALI - Adityatama, Ida Bagus Sedana; Urmila Dewi, Made Heny (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 11 No 7 (2020): VOL 11 NO 7, JULI 2022 [2481-2899], 2022)
Bali Province is one of the tourist destinations and there are also many wood carving crafts. The export level of wood carving handicrafts in Bali Province has fluctuated every year, the fluctuating export value of wood carving crafts is due to global economic conditions. This research was conducted in Bali Province. The type of data used is quantitative data with secondary data. Data collection was carried out through non-participant observation methods, which came from books, records and reports from related sources or agencies, namely the World Bank, the Bali Provincial Statistics Agency, the Bali Provincial Tourism Office, and the Bali Provincial Industry and Trade Office. The analysis technique used is multiple linear regression using time series data from 1996-2019. The results of data analysis show simultaneously the US dollar exchange rate, tourist visits, length of stay of tourists, and the average tourist expenditure have a significant effect on the export of wood carving handicrafts in Bali Province. Partially, the US dollar exchange rate and the length of stay of tourists have a negative effect, but tourist visits and the average tourist expenditure have a positive and significant effect on the export of wood carving handicrafts in Bali Province. Keywords : Export, US Dollar Exchange Rate, Tourist Visit, Long Stay of Tourists, Average Tourist Expenditure